Lubok 7 - Ruckhäberle, Christoph; Siemon, Thomas (Leipzig : Lubok Verlag, 2008)
Uta Koslik, Wolfgang Ellenrieder, Karl-Georg Hirsch, Franziska Leonhardi, Corinne von Lebusa, Jens Schubert, Sophie von Stillfried, Thomas Müller, Brian Montuori, Reiner Schlamp
Exemplar No.: 204/700
boek